Eugène Rodolphe Faribault: Nova Scotia Gold Icon - Mossman, David (Geoscience Canada, 2024)
Eugène Rodolphe Faribault proved to be a very good choice as a geologist for the Geological Survey of Canada, after his appointment on July 1, 1883. His career spanned fifty years, time mostly committed to mapping the southwestern half of Nova Scotia, concentrated on the slate and quartzite of the Meguma Supergroup in which gold mining was taking place. In his words, he was, “a specialist on geological maps and structural geology of gold mines in Nova Scotia”. Dozens of his meticulously prepared maps of over sixty gold districts have stood the test of time for accuracy. A popular figure in the field, Faribault made frequent trips to operating mines. He early recognized the existence, in some districts, of extensive bodies of low-grade ore. He emphasized too, the similarities between the ‘saddle reef’ deposits mined in the Bendigo fields of Australia and the auriferous veins of the Meguma formations. His ‘pay-zone’ theory held that near-surface mineable ore in Nova Scotia gold mines should continue at depth, provided the same structural conditions persisted. However, for various reasons his theory received a mixed reception.Back in Ottawa at the GSC offices, Faribault was a highly respected figure among fellow workers and supervisors alike, and across all departments. His quiet charisma and friendly nature, complemented by professional expertise, won him accolades as an ambassador well beyond the workplace. For his excellence in a young developing science, Faribault thoroughly earned the epithet, “The Grand Old Man of Nova Scotian Geology”.